Serum Vitamin D Status and its Relationship with Metabolic Parameters in Patients with Type 2 Diabetes Mellitus - Islam, Md Tazul; Nargis, Susmita; Roy, Heera Lal; Islam, Ehsanul; Sultana, Mahmuda; Mahmud, Sarker Hafiz (Mediscope, 2022)
Vitamin D is a fat-soluble vitamin with hormonal functions, which helps in calcium and phosphate homeostasis and bone metabolism. Beyond the role in bone health, vitamin D influences non-skeletal health problems and chronic diseases like obesity, hypertension, cardiovascular diseases, glucose intolerance and type 2 diabetes mellitus (T2DM). Low vitamin D impairs insulin synthesis and secretion resulting in glucose intolerance in T2DM. This study was carried out between July 2015 to June 2016 to assess vitamin D status in T2DM patients. In this study, vitamin D {25-hydroxycholecalciferol [25(OH)D3]} was assessed in 65 type 2 diabetes mellitus patients and 70 healthy subjects of matching age and sex. Serum 25-hydroxycholecalciferol, fasting blood glucose (FBG), total cholesterol and serum creatinine were estimated. Data were analyzed with the help of the statistical package “R” (version 2.7). Serum 25-hydroxycholecalciferol in cases (Group A) was 55.73±9.02 ng/ml and in controls (Group B) was 53.77±10.86 ng/ml; there was no statistically significant difference between the two groups. Serum FBG was significantly different between the two groups, whereas serum total cholesterol and serum creatinine were not significantly different between the two groups. In type 2 diabetes patients, no significant correlation was found between serum 25-hydroxycholecalciferol with Body mass index (BMI), fasting blood glucose and total cholesterol. In healthy controls, there was no significant correlation of serum 25-hydroxycholecalciferol with BMI, fasting blood glucose and total cholesterol. Vitamin D level was sufficient in both type 2 diabetes patients and healthy individuals. Vitamin D was not associated with T2DM. Mediscope 2022;9(2): 75-80